A81 POOLED SAFETY ANALYSIS FROM THE USTEKINUMAB CROHN'S DISEASE AND PSORIATIC DISEASES PHASE 2 AND 3 TRIALS. (1st March 2018) - Feagan, B G; Sands, B E; de Villiers, W; Ott, E; Gasink, C; Lang, Y; Szapary, P; Jacobstein, D; Ghosh, S
Abstract: Background: Ustekinumab (UST) is well-established in psoriasis (PsO) & psoriatic arthritis (PsA) with up to 5 years safety data from psoriasis clinical trials with 3117 pts & 8998 patient years (PY). However, limited safety data have been presented in Crohn's disease (CD). In CD, Phase 2/3 data show that UST is safe & effective. Aims: Here we present CD safety data & compare it to safety from psoriatic diseases. Methods: Safety data from 5 CD (2 Ph2/3Ph3) trials were analyzed with the previously reported PsO (1 Ph2/3Ph3) & PsA (1 Ph2/2 Ph3) trials. Psoriatic pts received UST 45 or 90mg SC; Ph3 CD pts received one IV UST dose (130mg or ~6 mg/kg) then 90mg SC q8w or q12w. Permitted concurrent treatments differed by indication: PsO – none; PsA – methotrexate; CD - immunosuppressives & corticosteroids. All pts who received ≥1 dose of UST were included. Outcomes are presented as events per 100 PY. Results: In the PBO-control period, 3636 pts received UST (1582 PsO, 692 PsA & 1362 CD). Treated pts with ≥1 reported event PBO vs UST in pooled indications (events/100 PY): AEs 556.1 vs 594.3; SAEs 19.5 vs16.4; infections 135.8 vs138.1; serious infections 2.9 vs 3.3; MACE 0.26 vs 0.60; malignancies 0.26 vs 0.12; deaths 0 vs 0.12. Through 1 year, 5884 pts received UST (3117 PsO, 1018 PsA, & 1749 CD) over 4521 PY. Rates of AEs, SAEs, & infections were similar between UST & PBO (Table) across all groups. Event rates in the combined CD studies were also similar between groups with more frequent overall AEs, & infections in CD pts. Conclusions: UST has a favorable safety profile in CD with one IV induction dose up to 6mg/kg & SC maintenance up to 90mg q8wks. Evaluation of the CD experience did not alter the safety profile of UST established in pts with psoriatic disease treated up to 5 years. Funding Agencies: Janssen Research & Development, LLC